2022
DOI: 10.1530/rep-21-0354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palmitic acid on localization of embryo cell fate and blastocyst formation gene products

Abstract: As obese and overweight patients commonly display hyperlipidemia, and are increasingly accessing fertility clinics for their conception needs, our studies are directed at understanding the effects of hyperlipidemia on early pregnancy. We have focused on investigating palmitic acid (PA) and oleic acid (OA) treatment alone and in combination from the mouse two-cell stage as a model for understanding their effects on the mammalian preimplantation embryo. We recently reported that PA exerts a negative effect on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…It has been established that the exogenous supply of FAs in culture medium can affect reproductive potential, such as oocyte maturation, cryopreservation, oxidative stress, and cellular signaling, in various species 35 37 . Furthermore, an excessive amount of FAs, especially saturated FAs, reportedly resulted in reticulum stress, lower fertilization and embryo development rates, and caused irreversible damage to fetal growth and offspring health 38 43 . However, the concentration of FAs in the warming solution used in this study was much lower (approximately 1/1000) than those in previous studies that demonstrated the detrimental effects of FAs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the exogenous supply of FAs in culture medium can affect reproductive potential, such as oocyte maturation, cryopreservation, oxidative stress, and cellular signaling, in various species 35 37 . Furthermore, an excessive amount of FAs, especially saturated FAs, reportedly resulted in reticulum stress, lower fertilization and embryo development rates, and caused irreversible damage to fetal growth and offspring health 38 43 . However, the concentration of FAs in the warming solution used in this study was much lower (approximately 1/1000) than those in previous studies that demonstrated the detrimental effects of FAs.…”
Section: Discussionmentioning
confidence: 99%